2020
DOI: 10.3389/fmats.2020.587580
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Mechanical Behavior of Bamboo-Concrete Connections and Wood-Concrete Connections

Abstract: To investigate the similarities and differences of mechanical behavior between the bamboo-concrete connections and the wood-concrete connections, thirty-six specimens were tested through push-out tests with the material type (bamboo or wood), concrete strength and dowel diameter as test parameters. In addition to the linear variable displacement transducer the digital image correlation was also used to obtain the slip distribution of the whole field of the specimens, which was conducive to the further detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…An experimental study of bamboo-concrete and wood-concrete connections was conducted by Wang et al [74] to investigate their similarities and differences in mechanical properties. Bamboo-concrete connections were found to have a 19% higher shear stiffness than wood-concrete connections.…”
Section: Connectionsmentioning
confidence: 99%
“…An experimental study of bamboo-concrete and wood-concrete connections was conducted by Wang et al [74] to investigate their similarities and differences in mechanical properties. Bamboo-concrete connections were found to have a 19% higher shear stiffness than wood-concrete connections.…”
Section: Connectionsmentioning
confidence: 99%
“…Otro estudio comparó el comportamiento entre la unión mediante pasadores internos de madera-hormigón armado y bambú-hormigón armado. Ambas muestras tuvieron un comportamiento similar en los modos de fallo y en el desplazamiento (Wang et al, 2020). La falla fue moderada, dado que las probetas mostraron grandes deformaciones plásticas antes de fallar y el hormigón también presentó grietas, lo que indicó el aporte uniforme de los materiales de la unión.…”
Section: Uniones Con Perforaciones En El Culmounclassified
“…They summarized the failure mode of the composite beam and the effect of the layer number and thickness of BFRP plate on the flexural bearing capacity of the composite beam. Wang et al (2020aWang et al ( , 2020b, Wei et al (2021) studied the bending behavior of bamboo beams composed of different connectors and concrete and found that the stiffness of composite beams can be increased by 4.16 times compared with the base beam. Wei et al (2015) proposed that nearsurface mounted steel bars could be used to strengthen glulam bamboo beams.…”
Section: Introductionmentioning
confidence: 99%